ANALISIS EFEKTIFITAS PENGGUNAAN WEB-BASED-LEARNING PADA MATAKULIAH PRAKTIKUM STRUKTUR DATA - Nurul Adha Oktarini Saputri; Merriayu Puspita Hannah (JUST IT : Jurnal Sistem Informasi, Teknologi Informasi dan Komputer, 2018)
This study aims to measure and examine how the effectiveness of the use of web base learning in the course practicum data structure. Web-based learning (web base learning) that will be used in this research is a web tutorial address www.tutorialspoint.com. While the programming language to be studied on the web tutorial is a C ++ programming language tutorial. The methodology used in this research is Research & Development with tutorial web-based instructional instructional products for practical data structure course. The result of this research is first that is learning with web base learning in practice subject which suitable to applied for new student group taking the course and the student who repeat the course. Second, the perception of the effectiveness of learning with web-based learning is higher in the group of students whose long internet access is high and in the group of students who study while working. Third, found the influence of the effectiveness of the use of web base learning in learning to learning outcomes. Keywords: Web base-learning, The effectiveness, C ++ Language.